2024
DOI: 10.1111/apt.17869
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: Steatosis severity and subclinical atherosclerosis in metabolic dysfunction‐associated steatotic liver disease

Mohamad Jamalinia,
Fatemeh Zare,
Kiarash Noorizadeh
et al.

Abstract: SummaryBackgroundMetabolic dysfunction‐associated steatotic liver disease (MASLD) is a prevalent liver condition recognised as an independent risk factor for cardiovascular disease (CVD). However, there is ongoing debate regarding the effective strategy for cardiovascular risk assessment in MASLD.AimTo investigate the relationship between liver imaging, specifically focusing on the severity of steatosis and subclinical atherosclerosis.MethodsWe conducted a thorough search across four databases, from 1950 to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recent research has revealed a correlation between metabolic dysfunction-associated steatotic liver disease (MASLD) and an increased risk of atherosclerosis [12][13][14][15]. This risk escalates proportionally with the severity of MASLD, particularly as brosis progresses [16,17]. Simultaneously, atherosclerosis emerges as a signi cant risk factor for the advancement of AAAs, thereby heightening the mortality risk among affected individuals [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed a correlation between metabolic dysfunction-associated steatotic liver disease (MASLD) and an increased risk of atherosclerosis [12][13][14][15]. This risk escalates proportionally with the severity of MASLD, particularly as brosis progresses [16,17]. Simultaneously, atherosclerosis emerges as a signi cant risk factor for the advancement of AAAs, thereby heightening the mortality risk among affected individuals [18,19].…”
Section: Introductionmentioning
confidence: 99%